Network Pharmacology and Absolute Bacterial Quantification-Combined Approach to Explore the Mechanism of Tianqi Pingchan Granule Against 6-OHDA-Induced Parkinson’s Disease in Rats - Liu, Zhihua; Zhao, Jiahao; Yang, Shuyuan; Zhang, Yu; Song, Lu; Wu, Na; Liu, Zhenguo (Frontiers in Nutrition, 2022)
Parkinson’s disease (PD) is the second most common neurodegenerative disease. Tianqi Pingchan Granule (TPG) is a clinically effective formula of traditional Chinese medicine to treat PD. However, the therapeutic effect and underlying mechanisms of TPG in PD remain unclear. Based on network pharmacology, the corresponding targets of TPG were identified using TCMSP Database. Deferentially expressed genes in PD were obtained from the TTD, OMIM, Genecards and DrugBank database. The protein–protein interaction (PPI) networks of intersected targets were constructed using the STRING database and visualized using Cytoscape. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed, and the pathways directly related to pathogenesis of PD were integrated manually. Furthermore, in vivo studies were carried out based on network pharmacology. The gut microbiota, peripheral inflammatory cytokines and glia-mediated neuroinflammation in substantia nigra were evaluated. 99 target genes were intersected between targets of TPG and deferentially expressed genes in PD. The PPI network analysis indicated that proinflammatory cytokine as essential targets. GO analysis and KEGG analysis indicated that inflammatory response and its related signaling pathways were closely associated with TPG-mediated PD treatment. In vivo studies we first revealed that class Negativicutes and order Selenomonadales decreased, while class Mollicutes, order Enterobacteriales and Mycoplasmatales increased in fecal samples of PD rats via 16S rRNA sequence analysis. Furthermore, the function prediction methods purposely revealed that TPG therapy may be involved in flavonoid biosynthesis, which have anti-inflammatory properties. In addition, in vivo studies revealed that TPG exposure was found to not only attenuate the production of peripheral inflammatory cytokines but also inhibit the activation of microglia and astrocytes in substantia nigra of PD rats.Through network pharmacology and in vivo experiment-combined approach, the mechanisms of TPG in the treatment of PD were revealed, and the role of TPG in the regulation of gut microbiota and inflammatory response was confirmed.